PENDAMPINGAN BIMBINGAN BELAJAR PADA SISWA SEKOLAH DASAR DI KELURAHAN KEPUH CIWANDAN - Fatari, Fatari; Prahima, Parko; Sari, Yunita; Nufauziah, Nufauziah; Rustia, Winda; Munawaroh, Munawaroh; Sthefani, Sthefani; Homsanah, Dede (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
This Community Service aims to provide tutoring assistance to State Elementary School students in the Kepuh sub-district, Ciwandan District during the KKM activities. The implementation method involves students directly visiting the State Elementary School in the Kepuh sub-district and coordinating with the school principal and teachers who have previously submitted permission letters. Students enter the classroom and carry out the tutoring assistance process, especially for grade 1 and grade 5-6 students. The learning assistance provided by KKM students is in the subjects namely English, Religion and Free Nalek. From the results of the tutoring assistance, the teachers at the school felt helped, and the students also felt happy and understood what had been taught. The students hoped that the mentoring and tutoring activities could be carried out continuously, but this could not be implemented considering that the KKM activities at that place only lasted 2 months